Aportes para un debate actual: Arte, cuerpo y lenguaje - Escudero , Carolina (Nómadas. Critical Journal of Social and Juridical Science, 2010)
The work aims to provide a reading of Adorno and Horkheimer, Benjamin and Nancy in a contemporary focus, that is, located in current debates about the relationship between body, language and art. The aim is to encourage critical reflection on these axes and to question in relation to certain elements common to the authors from the start dialogue between them. The horizon or background that motivates these reflections is located on the possibility of thinking and capture the experience of contemporary man, therefore, the reference to the problem of the subject, though often in a latent, is of paramount importance. In this broader context enroll final reflections, which help to systematize, in the key methodological elements that provide reading and bringing into play of these texts.